Universal van der Waals force between heavy polarons in superfluids - Fujii, Keisuke; Hongo, Masaru; Enss, Tilman (Physical review letters, 2022)
We investigate the long-range behavior of the induced Casimir interaction between two spinless heavy impurities, or polarons, in superfluid cold atomic gases. With the help of effective field theory (EFT) of a Galilean invariant superfluid, we show that the induced impurity-impurity potential at long distance universally shows a relativistic van der Waals-like attraction (∼1/r7) resulting from the exchange of two superfluid phonons. We also clarify finite temperature effects from the same two-phonon exchange process. ...